Distributed video coding using interval overlapped arithmetic coding - Zhou, Junwei; Fu, Yincheng; Yang, Yanchao; Ho, Anthony T.S. (Signal processing. Image communication, 2019)
Distributed video coding (DVC) is a flexible and novel video coding mode that is different from traditional video compression methods, which can shift the complex task such as motion estimation from encoder to decoder. Nowadays, most of the DVC architectures adopt channel coding such as low-density parity-check codes. It is found that arithmetic coding can be also extended to compress correlated sources and even has better performance than the channel coding for short to medium block length sources. Therefore, we propose a DVC scheme using interval overlapped arithmetic coding that is distributed arithmetic coding (DAC) without feedback channel, where the Key frames are compressed using traditional video coder while the Wyner–Ziv frames are compressed using DAC. We compare the rate–distortion performance of the proposed scheme with the state-of-the-arts, and the experimental results indicate that the proposed scheme is competitive. The source code for this scheme is available in GitHub. •Implement DVC using distributed arithmetic coding (DAC) instead of channel coding.•DAC has an advantage of compressing short to medium length data and adapting source.•The proposed scheme has higher PSNR with the same rate than existing schemes.